2020
DOI: 10.1073/pnas.2011641117
|View full text |Cite
|
Sign up to set email alerts
|

The dependency of red Rubisco on its cognate activase for enhancing plant photosynthesis and growth

Abstract: Plant photosynthesis and growth are often limited by the activity of the CO2-fixing enzyme Rubisco. The broad kinetic diversity of Rubisco in nature is accompanied by differences in the composition and compatibility of the ancillary proteins needed for its folding, assembly, and metabolic regulation. Variations in the protein folding needs of catalytically efficient red algae Rubisco prevent their production in plants. Here, we show this impediment does not extend to Rubisco from Rhodobacter sphaeroides (RsRub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 51 publications
2
46
0
Order By: Relevance
“…2018 ). Thus, together these results indicate that rubisco kinetic traits are perhaps not as inextricably linked as originally thought, and suggest that there is scope for increasing the catalytic efficiency of the enzyme as has happened in nature for rubisco in some red algae ( Andersson and Backlund 2008 ; Gunn et al. 2020 ).…”
Section: Introductionmentioning
confidence: 67%
“…2018 ). Thus, together these results indicate that rubisco kinetic traits are perhaps not as inextricably linked as originally thought, and suggest that there is scope for increasing the catalytic efficiency of the enzyme as has happened in nature for rubisco in some red algae ( Andersson and Backlund 2008 ; Gunn et al. 2020 ).…”
Section: Introductionmentioning
confidence: 67%
“…The unique phenotype of the AncIB strain could be a direct result of the ancestral RbcL subunit or due to impediments to the assembly and activationof a hexadecamer RuBisCO complex containing both the ancestral RbcL and modern RbcS subunits. Another possibility is hampered integration of ancestral RbcL given a modern suite of associated proteins required for RuBisCO folding and assembly (57). Further, while overexpression of the ancestral RbcL occurred at the level of transcription and translation, the ancestral strain appears to have comparable levels of assembled hexadecamer RuBisCO, suggesting lower rates of RuBisCO assembly (or faster degradation).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an updated examination of rubisco kinetics in the context of other enzymes has shown that it is not as inefficient a catalyst as often assumed (Bathellier et al ., 2018). Thus, together these results indicate that rubisco kinetic traits are perhaps not as inextricably linked as originally thought, and suggest that there is scope for increasing the catalytic efficiency of the enzyme as has happened in nature for rubisco in some red algae (Andersson and Backlund, 2008; Gunn et al ., 2020).…”
Section: Introductionmentioning
confidence: 69%